Pengaruh Terapi Spiritual Emotional Freedom Technique (Seft) terhadap Nyeri Dismenore Primer pada Remaja Putri - Wafiq Aurelia Novany; Leny Adifa; Rifatia Toto (Lembaga Pengembangan Kinerja Dosen, 2025)
Primary dysmenorrhoea is a reproductive health problem that is often experienced by adolescent girls. Primary dysmenorrhoea causes discomfort (pain) and other problems. If not treated immediately, it will interfere with learning, daily activities, and school performance. Efforts to treat primary dysmenorrhoea that can be done nonpharmacologically using SEFT therapy. This therapy combines spiritual, physical, and psychological. The purpose of this study was to determine the effect of SEFT therapy on primary dysmenorrhoea pain in adolescent girls. The method used was quasi experiment with non-equivalent control group design approach. Samples were selected using purposive sampling as many as 32 adolescents who were divided into intervention groups and control groups. The instruments used were pictorial SEFT therapy procedure, observation sheet, and Numeric Rating Scale (NRS). Data analysis used paired t-test and independent t-test. The results of the analysis showed a decrease in the pain scale in the intervention group with an average of 5.87 to 2.37 and bivariate analysis with a p-value of 0.000 (<0.05). So it can be concluded that there is an effect of SEFT therapy on primary dysmenorrhoea pain in adolescent girls.